Cytotoxicity of Buah Merah (Pandanus conoideus Lamk.) Extract on Breast Cancer Cell Line (T47D) - Tri R. Nuringtyas; Yoga Pratama; G. Galih; Subagus Wahyuono; Sukarti Moeljopawiro (Universitas Gadjah Mada, 2014)
Buah Merah (Pandanus conoideus Lamk.) has been extensively used to treat various diseases includingcancer. There are many varieties of buah merah and there was no scientifi c study comparing cytotoxicity ofdifferent varieties. The objective of this study was to investigate the cytotoxicity of three varieties of buah merahknown as Barugum, Maler and Yanggiru on breast cancer cell line (T47D). All samples were collected fromPapua, Indonesia. Each sample was extracted consecutively using three solvents chloroform, methanol andwater resulted to nine crude extracts. The cytotoxic activities were determined using MTT assay. The crudeextract showed the lowest IC50 was selected for further bioassay-guided fractionation. Fractionation was doneusing vacuum liquid chromatography coupled with preparative TLC to fi nd the active compounds. Severaldetection reagents were applied to TLC for identifi cation of the class of the potent compounds. The resultshowed that the potent extracts was obtained from Barugum methanol extract followed by Maler chloroformextract with IC50 value of 132.83 μg/ml and 139.72 μg/ml, respectively. All Yanggiru extracts did not showactivity. The bioassay-guided fractionation of Barugum and Maler extracts showed that the most potent fractioneluted by a mixture of hexane:ethyl acetate (75:25), was in Maler variety with IC50 value of 25,7 μg/ml, fourtimes higher than the most potent fraction of Barugum with IC50 value of 104,61 μg/ml. TLC analysis of themost potent fraction showed that the active compounds was class of terpene. Result of this study supportedthe utilization of buah merah Maler variety for breast cancer treatment.